2013
DOI: 10.1007/s00424-013-1256-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of PSD-95 in the rearrangement of Kv1.3 channels to the immunological synapse

Abstract: Establishment of the immunological synapse (IS) between T lymphocytes and antigen-presenting cells is a key step in the adaptive immune response. Several proteins accumulate in the IS, such as the Kv1.3 potassium channel; however, the mechanism of this translocation is unknown. PSD-95 and SAP97 are adaptor proteins that regulate the polarized cell surface expression and localization of Kv1 channels in neurons. We investigated whether these proteins affect the redistribution of Kv1.3 into the IS in non-excitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 41 publications
3
49
0
Order By: Relevance
“…37, 38 However, two recent reports identified PSD95 as a potentially important scaffold of K V 1 channels in lymphocytes and in cVSMCs. 16, 39 First, mutation of the K V 1.3 subunit PDZ binding motif or knockdown of PSD95 in T lymphocytes inhibited the recruitment of K V 1.3 into contact points on the cell surface, implying an important role of PSD95-K V 1 channel interaction in T-cell activation. 39 Second, we demonstrated in cVSMCs that PSD95 is expressed and antisense knockdown of PSD95 in rat CA for 72 hours results in a concomitant loss of K V 1 channel protein and vasodilator function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37, 38 However, two recent reports identified PSD95 as a potentially important scaffold of K V 1 channels in lymphocytes and in cVSMCs. 16, 39 First, mutation of the K V 1.3 subunit PDZ binding motif or knockdown of PSD95 in T lymphocytes inhibited the recruitment of K V 1.3 into contact points on the cell surface, implying an important role of PSD95-K V 1 channel interaction in T-cell activation. 39 Second, we demonstrated in cVSMCs that PSD95 is expressed and antisense knockdown of PSD95 in rat CA for 72 hours results in a concomitant loss of K V 1 channel protein and vasodilator function.…”
Section: Discussionmentioning
confidence: 99%
“…16, 39 First, mutation of the K V 1.3 subunit PDZ binding motif or knockdown of PSD95 in T lymphocytes inhibited the recruitment of K V 1.3 into contact points on the cell surface, implying an important role of PSD95-K V 1 channel interaction in T-cell activation. 39 Second, we demonstrated in cVSMCs that PSD95 is expressed and antisense knockdown of PSD95 in rat CA for 72 hours results in a concomitant loss of K V 1 channel protein and vasodilator function. These findings suggested a critical role of PSD95 in maintaining the expression of K V 1 channels in the cerebral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutational analysis of the conservative regions would be problematic since it has been demonstrated that simple point mutations of identical parts of Shaker channel can cause nonconducting channels [25,32]. On the contrary, relatively large perturbations in the distal C-terminus of the channel are well tolerated without a significant effect on the gating of Kv1.3 [57]. Therefore, we decided to study a mutant Kv1.3 which lacks the putative cholesterol motifs of the distal C-terminal.…”
Section: Discussionmentioning
confidence: 99%
“…If CHOL and 7DHC acts on these proposed receptor sites then Kv1.3ΔC should be CHOL and 7DHC insensitive. Previously, we showed that biophysical characteristics of the mGFP-Kv1.3-WT and mGFP-Kv1.3ΔC are identical; removal of the C-terminal did not change significantly the gating properties of Kv1.3 [57]. mGFP-Kv1.3-WT and mGFP-Kv1.3ΔC expressing CHO cells were loaded using 420 μM CHOL and 7DHC, and ionic currents were measured in outside-out patch configuration.…”
Section: Comparison Of Chol and 7dhc Loadingmentioning
confidence: 99%
See 1 more Smart Citation